EFEKTIVITAS THE 5E LEARNING CYCLE MODEL DENGAN PENDEKATAN INKUIRI BERBASIS ICT (INFORMATION & COMMUNICATION TECHNOLOGY) DALAM PEMBELAJARAN CHASSIS OTOMOTIF - Nugroho, Cahyo Aji (Jurnal Nosel, 2013)
The purpose of this research is to know the effectiveness of inquiry 5e learning cycle model based on ICT on learning outcomes and students? activity in teaching automotive chassis in class XII SMK Pancasila in 2012/2013 academic year. Related to the objective of the research, the research used experimental method. The research design used is Quasi- Experimental Design with Pretest- Posttest and Control Group. The total number of population is 120 students coming from four classes. The sampling of the research is cluster random sampling. From the population, two classes/ clusters were taken randomly as the sample so there are two classes in this research, experimental and control groups. Experimental group used inquiry 5e learning cycle model based on ICT, Control group used lecture model based on ICT. Technique of the data collection consist of test and obsrvation letter.The data are analyzed by using t-test formula (t-test for independent sample). In this case, data which are analyzed are pre-test and post-test scores of the two groups. The result of t-test in post-test computation shows that t observation (t0) is 3.73. Value tt with degree of freedom 48 of t table (tt) = 2.00. In this case, to = 3.73 is higher than tt = 2.00 (to > tt). From the result, there are significant difference learning outcomes between using inquiry 5e learning cycle model based on ICT and by using lecture based on ICT. Observation result from observer concluded, there are significant difference on the students? activity of chassis automotive between the students? taught by using inquiry 5e learning cycle model based on ICT and those taught by using lecture based on ICT. The experimental group show that students? activity better than control group.Based on the research finding above, it can be concluded that Inquiry 5e Learning Cycle Model Based on ICT is effective to learning outcomes and students? activity in teaching automotive chassis in class XII SMK Pancasila in 2012/2013 academic year.